ANALISIS PENGARUH IKLAN DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi pada konsumen Sariayu di Semarang) - Deatami, Nadia Maudita; Khasanah, Imroatul (Diponegoro Journal of Management, 2019)
The purpose of this study to analyze the effect of advertising and product design on purchasing decisions using brand image as an intervening variable. Using ad marketing and product design strategies, by looking at the condition of the cosmetics industry market in Indonesia which is increasing quite large, to the decline in sales spent by Sariayu cosmetics brands, as well as looking at sales data and Top Brand Index data in recent years.The population of the study was all consumers who had ever done to use Sariayu products. The samples in this study were 102 respondents. The method of collecting data through questionnaires directly with purposive sampling method. The provisions used are consumers who have purchased products more than once, at least 17 years old, and domiciled in Semarang. This research uses Structural Equation Modeling (SEM) analysis technique using AMOS 24.0 analysis tool.The result show that the effect of advertising has a positive and significant effect on brand image, product design has a positive and significant effect on purchasing decisions, the influence of advertising has a positive and significant effect on purchasing decisions, and product design has a positive effect and significant towards purchasing decisions.